Basement membrane protein nidogen-1 is a target of meprin β in cisplatin nephrotoxicity. Issue 2 (16th July 2015) - Herzog, Christian; Marisiddaiah, Raju; Haun, Randy S.; Kaushal, Gur P.
Highlights Basement membrane protein nidogen-1 is cleaved in cisplatin-induced nephrotoxicity. Meprin inhibitor actinonin abolished nidogen-1 cleavage during cisplatin nephrotoxicity. Meprin β-KO mice subjected to cisplatin nephrotoxicity prevented nidogen-1 cleavage. This study provides the first in vivo evidence of nidogen-1 cleavage by meprin β and a pathophysiological link between meprin β and nidogen-1 in cisplatin nephrotoxicity.